Parental behaviors and locus of control in raising children with autism - Sta. Ana, Nicole Marie S.
The study examined the locus of control (LOC) and behaviors of parents raising children with autism (CWA) to determine whether these parents have an internal or external LOC. It aimed to identify the parental LOC domains where they feel they have influence or experience a sense of ineffectiveness, and their methods for supporting the CWA's development, including discipline and adaptation strategies.